Association between dietary caffeine, coffee, and tea consumption and depressive symptoms in adults: A systematic review and dose-response meta-analysis of observational studies - Torabynasab, Kimia; Shahinfar, Hossein; Payandeh, Nastaran; Jazayeri, Shima (Frontiers in Nutrition, 2023)
Background Recent studies have reported an association between dietary caffeine intake (coffee and tea) and the presence of depressive symptoms. However, the findings are not conclusive. Purpose This study aimed to examine the correlation between the consumption of dietary caffeine (coffee and tea) and the presence of depressive symptoms in adults. Methods PubMed and Scopus databases were searched until December 2021. Two investigators analyzed data from identified studies and rated the quality of the evidence using the GRADE approach. Using the random-effects models, we estimated the relative risks (RRs) and 95% confidence intervals (CIs). We also modeled the dose-response associations through a one-stage, weighted mixed-effects meta-analysis. Results A total of 29 eligible studies included a total of 422,586 participants. On comparing the highest with the lowest category in cohort studies, we identified an inverse association between the intake of coffee and depressive symptoms (RR: 0.89, 95%CI: 0.82–0.95; I2 = 63.7%, GRADE = low). There was a 4% reduction in the risk of depression associated with an increase in coffee intake of 240 ml/day (RR: 0.96, 95%CI: 0.95, 0.98; I2 = 22.7%). By comparing the highest category with the lowest category in cohort studies, we discovered that caffeine intake was inversely associated with depressive symptoms (RR: 0.86, 95%CI: 0.79, 0.93; I2 = 0.0%, GRADE = moderate). Based on our data analysis, no correlation exists between tea consumption and depressive symptoms. Conclusion According to our findings, coffee and dietary caffeine may have a protective effect against the development of depression. However, no evidence suggesting a link between tea consumption and reduced depressive symptoms has been found. Therefore, further longitudinal studies are needed to substantiate the causal relationship between coffee, tea, and caffeine and the risk of depression.